JÜRG GLAUSER, PERNILLE HERMANN, STEPHEN A. MITCHELL (eds.): Handbook of Pre-Modern Nordic Memory Studies. Interdisciplinary approaches. Walter de Gruyter, Berlin and Boston, Mass., 2018. 2 vols (I: pp. xxvi + 940; II: pp. vii + 223). 54 figs, 7 tables, 26 colour plates. ISBN 978-3-11-044020-1. Issue 1 (2020) - McTURK, RORY
No abstract available